Isolation, Identification, Spectral Studies and X-ray Crystal Structures of Two Compounds from Bixa orellana, DFT Calculations and DNA Binding Studies - Parveen, Mehtab (2022)
4,6-Diacetylresorcinol (1) and 3-O-methylellagic acid dihydrate (2), both biologically significant compounds, were extracted from Bixa orellana and studied using IR, 1H, and 13C NMR, and UV-vis spectroscopic techniques. X-ray crystallographic techniques were also used to establish the molecular structure of the isolated compounds 1 and 2. Geometric parameters, vibrational frequencies, and gauge including atomic orbital (GIAO) 1H and 13C NMR of 1 and 2 in the ground state were computed by the density functional theory (DFT) using B3LYP/6-311G(d,p) basis set backing up experimental studies and established the correct structure of isolated compounds. The parameters obtained from the combined DFT, and X-ray diffraction studies are mutually agreed to establish correct structures of 1 and 2. In addition, an electrostatic potential map and HOMOLUMO energy gap were made using the DFT calculation to determine the distribution of energy and the chemical reactivity region of the isolated compounds. The current study also provides further insights into the interaction of compound 2 with ct-DNA using numerous biophysical and in silico techniques. Moreover, in silico studies indicate that compound 2 binds to the DNA in the minor groove. Lipinski’s rule of five revealed a higher tendency of compound 2 towards drug-likeness. The bioavailability and synthetic accessibility score for compound 2 was found to be 0.55 and 3.21, suggesting that compound 2 could serve as an effective therapeutic candidate.